Fangcang Shelter Hospitals for COVID-19 construction and operation manual - Yan, Zhi; Yan, Ge (World Scientific, 2020)
"A novel public health concept, the Fangcang Shelter Hospital was first proposed by Professor Wang Chen, an academician of Chinese Academy of Engineering, in Wuhan, China, in February 2020. While responding to the coronavirus disease 2019 (COVID-19) outbreak, medical staff faced the pressing situation of limited medical supplies, which led Professor Wang Chen to the suggestion of converting large-scale public venues such as exhibition centers and indoor stadiums into shelter hospitals to receive large number of patients, as this involved minimum time and monetary costs. The five essential functions of Fangcang Shelter Hospitals (isolation, triage, provision of basic medical care, frequent monitoring and rapid referral, and essential living and social engagement) enable shelter hospitals to receive patients with mild to moderate symptoms of COVID-19, and have the greatest impact on isolating the source of infection and expanding the area's health-care capacity.Two of the first three Fangcang Shelter Hospitals set up in Wuhan were redeveloped by Zall Group Property from existing buildings, while Zall Foundation was responsible for the provision of essential medical supplies and logistical support to facilitate the running of these shelter hospitals. In total, the two shelter hospitals have been instrumental in diagnosing, treating and curing 3663 patients. Under the medical expertise and guidance of Professor Wang Chen, as well as inputs from Zall Foundation's crews who contributed to the design, renovation and operation of these shelter hospitals, this manual encompasses knowledge and experience distilled from the running of these Fangcang Shelter Hospitals. Covering five important aspects, namely the proposal, design, renovation, operation, and logistical support for shelter hospitals, this booklet aims to be a useful reference for other epidemic prevention and control efforts in regions around the world. The manual has been translated into more than 20 languages